2020
DOI: 10.1038/s41398-020-00874-7
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-blood expression of inflammasome- and glucocorticoid-related mRNAs correctly separates treatment-resistant depressed patients from drug-free and responsive patients in the BIODEP study

Abstract: The mRNA expression signatures associated with the ‘pro-inflammatory’ phenotype of depression, and the differential signatures associated with depression subtypes and the effects of antidepressants, are still unknown. We examined 130 depressed patients (58 treatment-resistant, 36 antidepressant-responsive and 36 currently untreated) and 40 healthy controls from the BIODEP study, and used whole-blood mRNA qPCR to measure the expression of 16 candidate mRNAs, some never measured before: interleukin (IL)-1-beta, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 74 publications
(107 reference statements)
4
56
0
Order By: Relevance
“…Evidence suggests that at around 30% of patients with depression do not respond to antidepressant treatment, with most of them having sub-chronic levels of inflammation [1][2][3], a process which potentially impacts depression-relevant brain pathways. However, despite the role of inflammation in depression, there is still a lack of anti-inflammatory strategies that are effective for these patients, safe for everyday use, and with a clear mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that at around 30% of patients with depression do not respond to antidepressant treatment, with most of them having sub-chronic levels of inflammation [1][2][3], a process which potentially impacts depression-relevant brain pathways. However, despite the role of inflammation in depression, there is still a lack of anti-inflammatory strategies that are effective for these patients, safe for everyday use, and with a clear mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding immunological complexity, studies have reported various associations of serum inflammatory proteins with depression, including among others CRP, interleukin (IL)-6, IL-10, and tumour necrosis factor (TNF)-α (Goldsmith et al, 2016;Haapakoski et al, 2015;. Evidence from in-depth immunophenotyping further suggests that there may be distinct subgroups of inflammation-related depression as shown by immune cell count clustering and transcriptome analyses (Cattaneo et al, 2020;Lynall et al, 2020). These studies suggest that acutely elevated levels of inflammatory markers are associated with depression, but associations of depression with genetic/lifetime predisposition to higher inflammatory markers has been studied less frequently and primarily for CRP (Badini et al, 2020;Kappelmann et al, 2020;Milaneschi et al, 2017bMilaneschi et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic polymorphisms within the gene were found to be significantly associated with MDD (Zhao et al, 2020). Similarly, there are reports of increased A2M expression in the whole blood of MDD patients (Cattaneo et al, 2020). Other genes worth highlighting include CRYBA1, GALR3, GPR88, and DDC-AS1.…”
Section: Lessons On Pathophysiologymentioning
confidence: 83%